The Impact of Dependent Behavior on the Design of Classroom Evacuation Exits for Intellectually Disabled Students - Xiaochen Zhao; Guo Li; Zhiyi Tao; Yongbo Feng; Hu Zhang; Ming Liu; Xiaohu Jia; Yue Ma; Lipeng Chang; Yongfa Mei (Buildings)
The increasing demand for special education in architectural design highlights the urgent need to ensure the safe evacuation of students with intellectual disabilities. However, current research on classroom evacuation for these students remains limited, particularly concerning critical factors, such as the number, location, and distance of exits. This study investigated the impact of dependent behavior on classroom exit design for students with intellectual disabilities by developing a Cellular Automaton (CA) model based on their behavioral characteristics. Simulated evacuation scenarios, considering and disregarding dependent behaviors, were analyzed to assess their effects on the number and positioning of exits, and a predictive model was implemented to establish the relationship between exit spacing and evacuation time. The results indicated that the dependent behavior significantly reduced evacuation efficiency and substantially affected classroom exit design. Considering the dependent behavior, this study demonstrated that setting two exits reduced the average evacuation time for students with intellectual disabilities by 12.99%, with further reductions achieved by placing the exits at the rear rather than at the sides or front of the classroom. The research also revealed that under the influence of dependent behavior, the average evacuation time initially decreased and then increased as the distance between exits increased. As one of the few studies addressing evacuation issues for students and the first to incorporate dependent behavior into the evacuation model, this study provides valuable recommendations for classroom designs that balance evacuation safety and daily usability. It offers essential data to inform architectural designs for classrooms serving students with intellectual disabilities and serves as a reference for future educational building design standards and regulations.